El sistema de salud en Cuba: origen, doctrina y resultados - Salim Lamrani (Études Caribéennes)
Since the advent of the Cuban Revolution in 1959, Cuba has made health a national priority and built a public, universal and free system, placing the patient at the center of the medical project. Based on prevention and the concept of “family doctor”, it has enabled the population to benefit from a level of health protection unique to a Third World country, and to achieve indicators comparable to those of the most developed nations. Recognized by international institutions as being the preeminent model for developing countries, the Cuban health system is considered by some observers as a potential source of inspiration for the richest nations, in particular thanks to its preventive model. In addition to caring for its own citizens, Cuba has been providing medical expertise around the world for more than half a century and treating populations on all continents, making this service its primary source of income.